Role of adenosine receptors in mediating inflammatory cytokines in hyperglycemic muller cells / Selvakumar Mararajah - Selvakumar , Mararajah (2015)
Diabetic retinopathy (DR) is one of the most common complications of diabetes, causing vision impairment and blindness. Adenosine is an endogenous purine nucleoside that is formed at sites of metabolic stress associated with injury or inflammation. Due to inflammation, pro-inflammatory and anti-inflammatory cytokines activated and its effects are being mediated through 4 types of receptors including A1, A2A, A2B and A3. These receptors are members of the G-protein coupled receptors (GPCR) which elicit signals to the downstream genes such as cAMP and Protein Kinase A (PKA). In turn, PKA (cAMP- dependent) phosphorylates cAMP responsive element binding protein (CREB) and leads to apoptosis. In the present study, we mimic the hyperglycemic condition by growing the cells high glucose to determine the presence of adenosine receptors in human Muller cells and the effect of its agonists and antagonists on inflammatory markers, PKA and apoptosis. Human Muller cells (MIO-M1) were cultured in low (5 mM) and high (25 mM) glucose with 10% FBS and 1% P/S. Cells were reduced to 0 % FBS for 18 hours then treated with various agonist and antagonist. The adenosine receptors were identified by immunocytochemistry and ELISA were used to measure the levels of TNF-α, ICAM, IL-1β. PKA level and apoptosis were studied by Western Blot and Tunnel Assay respectively. Four types of adenosine receptors (A1, A2A, A2B and A3) were identified in human Muller cells (MIO-M1). TNF-α content was significantly increased/decreased after agonist A1 and A3 treatment, but significantly decreased after agonist A2A and A2B treatment. There was no significant effect on IL-1β and ICAM-1. PKA levels were significantly increased after antagonist A2A and A2B treatment. Apoptosis was not detected after treating with various adenosine agonist and antagonist. As a conclusion, stimulation of human Muller cells with adenosine A2A agonist (CGS 21680) and adenosine A2B agonist (NECA) reduce the iv level of TNF-α when exposed to high glucose. While A1 adenosine agonist (CCPA) and A3 adenosine agonist (IB-MECA) both positively and negatively regulate the TNF-α in hyperglycemia. However, none of these agonists have any significant role in affecting ICAM-1 and IL-1β. PKA level was increased after adenosine antagonist A2A (SCH 58261) and antagonist A2B (PSB 603) treatment, but did not exert apoptotic effect on human Muller cells when exposed to high glucose.